GAMBARAN PERAN KELUARGA TERHADAP PENDERITA TBC DI WILAYAH KERJA PUSKESMAS KOTA DATAR KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA 2013 - farida farida; Eddy Syahrial; Lita Sri Andayani (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Tuberculosis (TB) is a cronik infeksius disease is contagious. Indonesia is ranked third after India and China in contributing to the number of TB cases in te world. The role of family is very effective and efficient in supporting the healing of tuberculosis patients because it is not put forward in the form of material reward in ret but motivated by the perceived family closeness by sincere devotion, patience, love, compassion and responsibility as the implementasi of the value of faith. This is descriptive study with a quantitative approach. Results quantitatively analyzed descriptively portrayed in the percentage. The samples taken were 44 respondents using total sampling technique. Results showed te majority of respondents were female as many as 59,1%. The majority of respondents were aged 44-49 years of age. Education respondents are mostly elementary school and majority of respondents work is a housewife. Respondents role in preventing tuberculosis in the middle category as 77,3%. Respondents role in the process of tuberculosis treatment in the middle category as 90,9%. Respondents in order to fulfill the role of nutrition in the middle category as 70,5%. Expected to families in order to improve the prevention of transmission of tuberculosis in the family. In addition to enhanced performance clinic Kota Datar health workers in providing information about tuberculosis and can empower family members of patient with tuberculosis to be an active part of te cure of tuberculosis.